PROBLEMS OF LOCAL PLUMB RECONSTRUCTION FROM LONG-TERM ASTROOPTICAL SETS - Khalyavina, L. Ya.; Borisyuk, T. Ye. (Одеські астрономічні публікації, 2007)
Problems of reconstruction of a local plumb variations from long sets of astrooptical observations are considered. The attempt of its practical realization on the data of latitude observations in Poltava with 3 astrometrical instruments is undertaken.